Long-term ticagrelor for secondary prevention in patients with prior myocardial infarction and no history of coronary stenting: insights from PEGASUS-TIMI 54. (7th December 2019) - Furtado, Remo H M; Nicolau, Jose C; Magnani, Giulia; Im, Kyungah; Bhatt, Deepak L; Storey, Robert F; Steg, P Gabriel; Spinar, Jindrich; Budaj, Andrzej; Kontny, Frederic; Corbalan, Ramon; Kiss, Robert G; et al.
Abstract: Aims: PEGASUS-TIMI 54 demonstrated that long-term dual antiplatelet therapy (DAPT) with aspirin and ticagrelor reduced the risk of major adverse cardiovascular events (MACE), with an acceptable increase in bleeding, in patients with prior myocardial infarction (MI). While much of the discussion around prolonged DAPT has been focused on stented patients, patients with prior MI without prior coronary stenting comprise a clinically important subgroup. Methods and results: This was a pre-specified analysis from PEGASUS-TIMI 54, which randomized 21 162 patients with prior MI (1–3 years) and additional high-risk features to ticagrelor 60 mg, 90 mg, or placebo twice daily in addition to aspirin. A total of 4199 patients had no history of coronary stenting at baseline. The primary efficacy outcome (MACE) was the composite of cardiovascular death, MI, or stroke. Patients without history of coronary stenting had higher baseline risk of MACE [13.2% vs. 8.0%, adjusted hazard ratio (HR) 1.41, 95% confidence interval (CI) 1.15–1.73, in the placebo arm]. The relative risk reduction in MACE with ticagrelor (pooled doses) was similar in patients without (HR 0.82, 95% CI 0.68–0.99) and with prior stenting (HR 0.85, 95% CI 0.75–0.96; P for interaction = 0.76). Conclusion: Long-term ticagrelor reduces thrombotic events in patients with prior MI regardless of whether they had prior coronary stenting. These data highlight the benefits of DAPT in prevention of spontaneous atherothrombotic events and indicate that long-term ticagrelor may be considered in high-risk patients with prior MI even if they have not been treated with stenting. ClinicalTrials.gov Identifier: NCT01225562.